Comparative analysis of bola-drb3 allelic variation to determine genetic diversity and disease resistance in kedah–kelantan (kk) and miyazaki wagyu cattle - Siti Hajar Afifah Hamrah (2025)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 55204 - Research Project. This study aimed to establish and validate a Polymerase Chain Reaction (PCR) assay for the amplification of the BoLA – DRB3 exon 2 region in Kedah – Kelantan (KK) and Miyazaki Wagyu cattle, providing a foundational step for comparing their immunogenetic diversity. Blood samples were collected from twenty clinically healthy animals (n = 10 per breed) in Kelantan, Malaysia. Genomic DNA was extracted and amplified using primers specific for BoLA – DRB3 exon 2. Agarose gel electrophoresis confirmed successful amplification in 19 out of 20 samples, yielding a primary amplicon of approximately 300 base pairs (bp), which aligns with the expected fragment size range for this locus. One Miyazaki Wagyu sample showed no amplification, likely due to technical issues. The consistent amplification across both breeds validates the employed primers and PCR protocol. This successful genotyping establishes the essential molecular groundwork for subsequent, high – resolution analyses such as sequencing, which are required to identify specific alleles and investigate their potential association with disease resistance in Malaysia’s tropical production environment.